2017
DOI: 10.1093/ndt/gfx060
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of miR-29b and miR-30c by vitamin D receptor activators contributes to attenuate uraemia-induced cardiac fibrosis

Abstract: VDRAs, particularly paricalcitol, attenuated cardiac fibrosis acting on COL1A1, MMP-2 and CTGF expression, partly through regulation of miR-29b and miR-30c. These miRNAs and miR-133b could be useful serum biomarkers for cardiac fibrosis and also potential new therapeutic targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 49 publications
1
28
0
Order By: Relevance
“…Of interest, VD failed to significantly modify VDR mRNA expression, which reinforces that VD inhibits the proteasomal degradation of VDR [19], a process that may be overactive in fibroblasts from the CD-damaged tissue. However, the possibility that VD down-regulates the expression of miRNAs involved in VDR reduction, as recently reported in lung fibroblasts and cardiac fibrosis [33,34], cannot be ruled out. Of interest, the reduced VDR levels detected in fibroblasts from damaged tissue of CD patients paralleled with an enhanced migration of these cells, and VD significantly prevented the enhanced migration.…”
Section: Discussionmentioning
confidence: 89%
“…Of interest, VD failed to significantly modify VDR mRNA expression, which reinforces that VD inhibits the proteasomal degradation of VDR [19], a process that may be overactive in fibroblasts from the CD-damaged tissue. However, the possibility that VD down-regulates the expression of miRNAs involved in VDR reduction, as recently reported in lung fibroblasts and cardiac fibrosis [33,34], cannot be ruled out. Of interest, the reduced VDR levels detected in fibroblasts from damaged tissue of CD patients paralleled with an enhanced migration of these cells, and VD significantly prevented the enhanced migration.…”
Section: Discussionmentioning
confidence: 89%
“…Recently, some studies found associations between 1,25(OH) 2 D 3 and cardiovascular disease (CVD), lung disease, and tuberculosis. 34,35 Panizo et al 36 found that in uremic cardiomyopathy, activation of 1,25(OH) 2 D 3 receptors weakens myocardial fibrosis by increasing the expression of some proteins, including MMP-2. In addition, supplementation of vitamin D in streptozotocin-induced diabetic mice improves endothelial function, 37 and induces increased expression of VEGF in vascular smooth muscle cells (VSMCs) by binding to the VDR, which acts as a transcription factor for the VEGF promoter.…”
Section: Discussionmentioning
confidence: 99%
“…VDR activators (such as calcitriol and paricalcitol) can inhibit the expressions of miR-29b and miR-30c in nephrectomized rats. These miRNAs seem to act on COL1A1, MMP-2, and CTGF expression, attenuating cardiac fibrosis [ 141 ]. In humans with moderate chronic kidney disease, paricalcitol treatment for 12 weeks reduces cytokines and microRNAs involved in atherosclerosis and inflammation [ 142 ].…”
Section: Microrna Nutrients Inflammation and Chronic Diseasesmentioning
confidence: 99%